The dose of granulocyte colony-stimulating factor administered following cytotoxic chemotherapy is not related to the rebound level of circulating CD34+ haemopoietic progenitor cells during marrow recovery - Martin, Simona; Voso, Maria Teresa; Hohaus, Stefan; Pförsich, Margit; Frühauf, Stefan; Goldschmidt, Hartmut; Hegenbart, Ute; Haas, Rainer (British journal of haematology, 1998)
We report on the RmetHuG-CSF (filgrastim)-related mobilization efficiency in 120 patients with multiple myeloma who received cytotoxic chemotherapy. Three schedules of G-CSF administration starting 24 h after the end of chemotherapy were used: (1) a standard dose of 300 μg/d until the completion of PBSC collection; (2) dose escalation from 300 to 600-1200 μg/d during marrow recovery; (3) 600 or 1200 μg/d starting 24 h after cytotoxic chemotherapy. As a result, the individual dose per kg bodyweight varied between 2.83 and 23.08 μg. No relationship was found between the dose of G-CSF administered and the peak level of circulating CD34+ cells or the CD34+ cell counts recorded over the entire collection period.
Elektronische Reproduktion der Druck-Ausgabe 25. Dezember 2001
Im Titel ist "+" hochgestellt
Gesehen am 23.04.2025